Noise Suppression of ECG Signal Using Optimized Digital Butterworth Bandpass Filter - Septian, Belen (AI Society & STMIK Indonesia, 2024)
ECG devices have been widely utilized by medical experts for cardiac health detection. It generates an analog signal that has intrinsic characteristics represented by PQRST waves. Each wave is useful for diagnostic purposes. However, ECG signal is prone to noise, particularly EMG noise. This noise occurs as a result of muscle contraction or sudden body movement of a subject. Several studies have been proposed to suppress the EMG noise on ECG. However, the complexity of an algorithm is a challenging task to be solved. Considering this problem, this research aims to suppress EMG noise using a low-complexity algorithm. To achieve this objective, a method of Butterworth bandpass filter DF-II has been proposed. The findings demonstrate that the proposed method improves SNR and signal power by 0.498dB and 0.006dBm/Hz respectively. It also demonstrates the capability to perform efficiently on a microcontroller unit.